Disinfection effect of nodal segments from Vanilla planifolia Andrews on the morphogenetic response of in vitro plants - Azofeifa Bolaños, José Bernal (2019)
Introduction. The aseptic establishment in laboratory conditions of wild type Vanilla planifolia has not been documented in any sterilization and regeneration protocols, nor has been evaluated the importance of disinfection to enhance the plant vigor. Objective. The aim of this experiment was to evaluate the effect of a double disinfection process (greenhouse and laboratory) on the morphogenetic response of nodal segments of vanilla during the establishment and in vitro multiplication. Materials and methods. Laboratory experiments were conducted during 2015 and 2016 at “Instituto de Investigación y Servicios Forestales (INISEFOR) de la Universidad Nacional (UNA)”, Heredia, Costa Rica. The culture medium used was Murashige and Skoog (MS). Six treatments were evaluated: 1) alcohol 70%/NaClO 0.35%; 2) kilol/NaClO 0.35%; 3) control/NaClO 0.35%; 4) alcohol 70%/HgCl2 0.2%; 5) kilol/ HgCl2 0.2% and 6) control/HgCl2 0.2%. Growth variables evaluated were: percentage of total, bacterial and fungal contamination; length, weight, and diameter of the shoot; number, length and weight of the roots. Results. The main genera of bacteria and fungi were Pantoea sp. (33%) and Fusarium sp. (12%). The best disinfection treatment was obtained with the use of kilol in the nursery and HgCl2 in the laboratory, where 100% pathogen-free explants were obtained. For this treatment, a significant increase of length and weight of the shoot, number and weight of the roots were achieved during the establishment. In the multiplication stage, the experimental groups in the aseptic condition showed significant higher values for the variables length and weight compared to the morphogenic response obtained for the green and vigourous in vitro plants in the condition of contamination. Conclusion. The disinfection treatments sequence represents the base line to the optimization of in vitro culture protocols of wild type relatives of V. planifolia, this constitutes a contribution for the ex situ conservation of unique materials and increases promising genetic material.